Structure of 2-keto-3-deoxy-6-phosphogluconate (KDPG) aldolase from Pseudomonas putida - Bell, B. J.; Watanabe, L.; Rios-Steiner, J. L.; Tulinsky, A.; Lebioda, L.; Arni, R. K. (Blackwell Munksgaard, 2003)
2-Keto-3-deoxy-6-phosphogluconate (KDPG) aldolase from Pseudomonas putida is a key enzyme in the Entner-Doudoroff pathway which catalyses the cleavage of KDPG via a class I Schiff-base mechanism. The crystal structure of this enzyme has been refined to a crystallographic residual R = 17.1% (R-free = 21.4%). The N-terminal helix caps one side of the torus of the (betaalpha)(8)-barrel and the active site is located on the opposite, carboxylic side of the barrel. The Schiff-base-forming Lys145 is coordinated by a sulfate (or phosphate) ion and two solvent water molecules. The interactions that stabilize the trimer are predominantly hydrophobic, with the exception of the cyclically permuted bonds formed between Glu132 OE1 of one molecule and Thr129 OG1 of a symmetry-equivalent molecule. Except for the N-terminal helix, the structure of KDPG aldolase from P. putida closely resembles the structure of the homologous enzyme from Escherichia coli.